2009
DOI: 10.1089/scd.2008.0152
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of STAT3 Signaling Pathway During Mouse Embryonic Stem Cell Differentiation

Abstract: Signal transducers and activators of transcription 3 (STAT3) is a pleiotropic transcription factor involved in a variety of physiological processes. STAT3 acts as a key transcriptional determinant of mouse embryonic stem (ES) cell self-renewal and plays a pivotal function in early mammalian embryogenesis because the development of many organs requires STAT3 activation. However, little is known about the role of STAT3 function during ES cell differentiation. To answer this question, we built a lentiviral constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Controversially to these reported data, other studies in ES cells point to STAT3 as an important factor for cardiomyogenesis within murine ES cells [86][87][88][89][90]. Whether this is a universal mechanism varies between species or depends on different laboratory conditions remains to be elucidated.…”
Section: Potential Role Of Stat3 In Regenerationmentioning
confidence: 99%
“…Controversially to these reported data, other studies in ES cells point to STAT3 as an important factor for cardiomyogenesis within murine ES cells [86][87][88][89][90]. Whether this is a universal mechanism varies between species or depends on different laboratory conditions remains to be elucidated.…”
Section: Potential Role Of Stat3 In Regenerationmentioning
confidence: 99%
“…And the effects of HIF-1α, EPO and VEGF on cell survival likely involve the expression of JAK2/STAT3 signal pathway, which plays a crucial role in regulation of inflammatory reaction [13], the growth and differentiation of cells [14], and cells apoptosis [15]. IL-6 is a member of the neuropoietin family of cytokines which includes leukemia inhibitory factor, ciliary neurotrophic factor, cardiotrophin oncostatin M, and IL-11 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A further understanding of the biochemical pathways involved in signaling transduction will hopefully provide new insights for the improvement of stem-cell based therapies. A number of previous studies have demonstrated that the inhibition of STAT3 activation by specific inhibitors drastically suppresses the differentiation of mESCs into cardiomyocytes induced by the coapplication of leukemia inhibitory factor and bone morphogenic protein 2 [50,51]. The involvement of activated STAT3 in the differentiation of BMSCs seems contradictory.…”
Section: Discussionmentioning
confidence: 99%